The Status of Workplace Violence in the United States: A Model for Prevention and Intervention - Moore, Linda Meliza (1999)
This paper examines the scope and causes of workplace violence, the second leading cause of death in the U.S. workplace today. A comprehensive review of existing literature is presented and a new model for prevention and intervention of workplace violence is proposed for use by practitioners. Suggestions for further data collection and research are presented so that further refinement can be made to workplace violence prevention and intervention models